2009
DOI: 10.1111/j.1468-3148.2009.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Violence on Staff Working with Adults with Intellectual Disabilities

Abstract: Background Staff in intellectual disability services can experience high levels of violence, which may lead to burnout. Staff burnout may result in poorer quality services. Previous research has suggested that factors such as fear of violence, self-efficacy and staff support moderate the impact of violence on burnout. Aims The research explores the relationship between levels of violence, with fear of violence, self-efficacy, staff support and burnout. Method A survey exploring levels of violence, fear of viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 46 publications
5
74
2
Order By: Relevance
“…The figure also shows the association between attributions and negative emotions as shown for specific attributions of controllability (Dagnan & Weston, 2006;Wanless & Jahoda, 2006) and internality (Dagnan & Cairns, 2005;Wanless & Jahoda, 2006). Although attributions and negative emotions appear to play a major role, other staff characteristics have been shown to be important, including coping resources (Mitchell & Hastings, 2001;Raczka, 2005;Robertson et al 2005;Whittington & Burns, 2005); more recently personality, as introduced by the quantitative studies (Chung & Harding, 2009;Lundström, Graneheim, Eisemann, Richter & Åström, 2007); and self-efficacy (Howard, Rose & Levenson, 2009). With regards to selfefficacy, the qualitative studies appear to allude to this construct with themes of powerlessness (Lundström, Åström & Graneheim, 2007), inadequacy (Fish, 2000) and feeling unable to manage challenging behaviour (Dagnan, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The figure also shows the association between attributions and negative emotions as shown for specific attributions of controllability (Dagnan & Weston, 2006;Wanless & Jahoda, 2006) and internality (Dagnan & Cairns, 2005;Wanless & Jahoda, 2006). Although attributions and negative emotions appear to play a major role, other staff characteristics have been shown to be important, including coping resources (Mitchell & Hastings, 2001;Raczka, 2005;Robertson et al 2005;Whittington & Burns, 2005); more recently personality, as introduced by the quantitative studies (Chung & Harding, 2009;Lundström, Graneheim, Eisemann, Richter & Åström, 2007); and self-efficacy (Howard, Rose & Levenson, 2009). With regards to selfefficacy, the qualitative studies appear to allude to this construct with themes of powerlessness (Lundström, Åström & Graneheim, 2007), inadequacy (Fish, 2000) and feeling unable to manage challenging behaviour (Dagnan, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Howard, Rose and Levenson (2009) suggests that a feeling of being able to manage challenging behaviour has more of an influence on burnout than exposure to challenging behaviour. Therefore it could be suggested that it is not the level of challenging behaviour which is stressful, but the way in which it is perceived.…”
Section: Quantitative Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interaction with clients may also be an additional source of stress. For example, employees who work with clients who engage in aggressive behaviors present a higher rate of burnout (Howard, Rose, & Levenson, 2009;Rose, Mills, Silva, & Thompson, 2013). Maslach et al (2001) found that younger employees tend to experience burnout more often than older employees.…”
Section: Behavioral Indicators and Causesmentioning
confidence: 99%